Myth or Magic? Towards a Revised Theory of Informed Consent in Medical Research. Issue 1 (14th January 2019) - Heinrichs, Bert
Abstract: Although the principle of informed consent is well established and its importance widely acknowledged, it has met with criticism for decades. Doubts have been raised for a number of different reasons. In particular, empirical data show that people regularly fail to reproduce the information provided to them. Many critics agree, therefore, that the received concept of informed consent is no more than a myth. Strategies to overcome this problem often rest on a flawed concept of informed consent. In this paper, it is suggested that informed consent is a communicative act between two persons. The challenge is to elucidate the norms and constraints for successfully performing such a communicative act. The view developed here has major consequences with regard to the standards for information disclosure as well as for the general scope of informed consent.